2023
DOI: 10.1049/itr2.12330
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐temporal correlation graph convolutional networks for traffic forecasting

Abstract: This is a repository copy of Spatial-temporal correlation graph convolutional networks for traffic forecasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…It should be noted that the experiments are based on historical data from the previous 60 min. That is, seq len takes the value 12 and predicts the traffic speed for the next (15,30,60) min, that is, pre len takes the values 3, 6, and 12, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that the experiments are based on historical data from the previous 60 min. That is, seq len takes the value 12 and predicts the traffic speed for the next (15,30,60) min, that is, pre len takes the values 3, 6, and 12, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Even though CNN is effective for capturing spatial features of traffic networks with a Euclidean architecture, it struggles to capture spatial features of traffic networks with a non-Euclidean architecture, which is the case for almost all traffic networks. To address this problem, a new approach, called GCN, 30,31,34,[39][40][41][42] has been introduced; it processes irregular data and captures spatial correlations efficiently. Zhao et al 18 benefited from the advantages of the GCN; they included a GRU and suggested a novel method, temporal GCN (T-GCN), for predicting the traffic status on urban roads.…”
Section: Spatial and Temporal Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above traffic-flow prediction providing typical time-series prediction is one of the essential parts of ITS, which is still a challenging issue. Over the past decades, various models and techniques were employed in traffic-flow prediction, which can be roughly divided into model-driven and data-driven approaches [16,17].…”
Section: Literature Reviewmentioning
confidence: 99%